The Effect of Financial Literacy and Financial Inclusion on MSME Financing Access Mediated by Financial Technology: Evidence from AC Service Entrepreneurs under Democare in Meruya Utara - Lutfi Alhazami; Dwi Sapto Febriantaka; Irma Rahmawati; Lisa Mangundap (Dinasti International Journal of Education Management and Social Science, 2026)
This study examines the effect of financial literacy and financial inclusion on MSME financing access, with financial technology (fintech) serving as a mediating variable among AC service entrepreneurs under Democare in Meruya Utara, West Jakarta. The research is motivated by limited formal financing for Indonesian MSMEs, which is only 38.4%, despite their 61.07% contribution to GDP. A quantitative approach using a cross-sectional survey was employed, involving 165 respondents selected via simple random sampling. Data were collected using a 5-point Likert scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that financial literacy and financial inclusion positively and significantly influence MSME financing access. Fintech acts as a partial mediator, strengthening the effect of literacy and inclusion on financing access. These findings highlight the importance of enhancing financial literacy, financial inclusion, and fintech adoption to improve MSME access to capital.